Effect of SCD probiotics supplemented with tauroursodeoxycholic acid (TUDCA) application on the aged rat gut microbiota composition - Ceylani, Taha (Oxford Univ Press, 2023)
Aims In this study, the effects of SCD Probiotics with tauroursodeoxycholic acid (TUDCA) application on the aged rat gut microbiota (GM) composition were investigated. Methods and results Twenty-four-month-old Sprague-Dawley rats were given 300 mg/kg of TUDCA along with 3 mL (1 x 10(8) CFU) of SCD probiotics for 7 days. The bacterial profile was determined by the metagenome applied to the cecum content. TUDCA, SCD probiotics, and TUDCA with SCD probiotics designed GM differently. TUDCA and SCD probiotics have the most different dominant species profiles. Conclusions SCD probiotics and TUDCA have their own unique effects on the species found in GM, and when they are evaluated together, the species found in GM are restructured differently.
Keywords: Tudca; Scd Probiotics; Gut Microbiota; Metagenomics; Sprague-Dawley Rat; Prebiotics; Dysbiosis; Health